Public Relations a wybrane pojęcia pokrewne - Kulig-Moskwa, Katarzyna (Public Relations and Marketing, Advertising and Corporate Social Responsibility, 2008)
The topic of the paper is discussion of the problem of relation and difference between public relations and marketing, advertising and Corporate Social Responsibility. Public relations and marketing are distinct function in an organization but Corporate Social Responsibility is part of public relations. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 120-129